Heterogeneous gene duplications can be adaptive because they permanently associate overdominant alleles. Issue 3 (1st August 2017) - Milesi, Pascal; Weill, Mylène; Lenormand, Thomas; Labbé, Pierrick
Abstract: Gene duplications are widespread in genomes, but their role in contemporary adaptation is not fully understood. Although mostly deleterious, homogeneous duplications that associate identical repeats of a locus often increase the quantity of protein produced, which can be selected in certain environments. However, another type exists: heterogeneous gene duplications, which permanently associate two (or more) alleles of a single locus on the same chromosome. They are far less studied, as only few examples of contemporary heterogeneous duplications are known. Haldane proposed in 1954 that they could be adaptive in situations of heterozygote advantage, or overdominance, but this hypothesis was never tested. To assess its validity, we took advantage of the well-known model of insecticide resistance in mosquitoes. We used experimental evolution to estimate the fitnesses associated with homozygous and heterozygous genotypes in different selection regimes. It first showed that balanced antagonist selective pressures frequently induce overdominance, generating stable polymorphic equilibriums. The frequency of equilibrium moreover depends on the magnitude of two antagonistic selective pressures, the survival advantage conferred by the resistant allele versus the selective costs it induces. We then showed that heterogeneous duplications are selected over single-copy alleles in such contexts. They allow the fixation of the heterozygote phenotype, providing an alternative and stable intermediate fitness trade-off. By allowing the rapid fixation of divergent alleles, this immediate advantage could contribute to the rarity of overdominance. More importantly, it also creates new material for long-term genetic innovation, making a crucial but underestimated contribution to the evolution of new genes and gene families.